Strategy Development to Promote Tourism in a Second Tiercity at Chiangkhan, Loei Province - Supromajakr, Intira; Putthongsri, Panruethai; Mahapornpong, Phromphong; Chusakul, Wisitsiri (Dhammathas Academic Journal, 2022)
This research is intended to 1) study current conditions, problems, and the wishes and need for the promotion of tourism in a second tier city at Chiangkhan, Loei Province. 2) develop strategies to promote tourism in a second tier city at Chiangkhan, Loei Province, and 3) implement the strategy for promoting tourism in a second tier city at Chiangkhan, Loei Province and evaluate the results of the implementation of the strategy. Participants of this research included entrepreneurial representatives, representatives of tourism agencies and tourists in Chiangkhan District. The research method which I utilized was the Participatory Action Research method (PAR). The research instruments used include in-depth interviews, group discussions, brainstorming meetings, and collaborative action. The results revealed that: Current conditions in Chiangkhan divide tourism into 4 elements (4As): 1. Attractions, 2. Accessibility, 3. Amenities and 4. Ancillary Service. However, the city is currently facing difficulties with attracting tourists, making tourist attractions accessible, supplying the necessary amount of amenities, and keeping the service of tourist attractions up to standard. To combat this, I wish to improve the quality of the personnels and tourist activities, the management of accessibility to tourist attractions and amenities, and enhance the service of tourist attractions to be up to standard. Results of the development of the strategy to promote tourism in a second tier city at Chiangkhan, Loei Province consist of the vision "Chiang Khan, a world-class sustainable tourist city, an environmentally friendly city of good health and leisure with advanced agriculture and a priceless local culture", 5 strategies, 5 missions, 5 goals, 14 strategies, 101 projects and 105 indicators. Results of the implementation of the strategic development to promote tourism in a second tier city at Chiangkhan, Loei Province and the evaluation of the implementation of the strategy, which includes 7 projects, were satisfactory to the participants. The satisfaction assessment results for the event venue and duration of the event, the participants’ understanding of the contents discussed, the practical application of the knowledge gained during the event, and the participants’ ability pass on the knowledge that they gained to others were all ranked at the highest level. Keywords : Tourism Promotion Strategy; Tourism; A second tier city